Tongue Nodule as Primary Manifestation of American Cutaneous Leishmaniasis in an Immunocompetent Patient - Botelho, Maria Clara Bertolini [UNESP]; Ferreira, Lígia Lavezo [UNESP]; Fikaris, Stelios [UNESP]; Prado-Ribeiro, Ana Carolina; Soubhia, Ana Maria Pires [UNESP]; Biasoli, Eder Ricardo [UNESP]; Miyahara, Glauco Issamu [UNESP]; Bernabé, Daniel Galera [UNESP] (Springer Nature, 2020)
Leishmaniasis is a parasitic disease considered an endemic public health problem in developing countries, where it is a reportable disease. Isolated oral manifestation is rare, and its clinical manifestations are variable. In this paper we describe an unusual case of an immunocompetent patient, 57-year-old man with a painless reddish submucosal nodule located on the tongue dorsum. Microscopical analysis showed chronic inflammatory infiltrate with macrophages containing leishmania in cytoplasmic vacuoles. PCR assays confirmed the diagnosis and patient was treated with meglumine antimoniate for 30 days. Absence of the parasite was confirmed by PCR. Thirteen years after treatment, a scar fibrosis persisted on the tongue dorsum. The case reported reveals that leishmaniasis should be considered in the diagnosis of tongue nodules in immunocompetent patients.
Keywords: Leishmaniasis; Meglumine antimoniate; Oral diagnosis; Oral mucosa; Scar fibrosis; Tongue nodule